1997
DOI: 10.1002/(sici)1096-9063(199704)49:4<353::aid-ps539>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Penetration and Symptomology Studies on Larvae ofDiabrotica undecimpunctata howardi(Barber)

Abstract: : The internal and external levels of topically applied soil insecticides, teÑuthrin, terbufos and dieldrin, to 3rd-instar larvae of the southern corn rootworm, Diabrotica undecimpunctata howardi (Barber), were monitored over 48 h. Symptomology of poisoning with 10 times the dose of the larval 72-h for LD 90 each chemical was observed over 48 h at various time points after treatment. Terbufos penetrated more rapidly than teÑuthrin or dieldrin, although internal levels of teÑuthrin and dieldrin had a longer-las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Although the synthetic blend elicited robust feeding by neonate larvae on tefluthrin, the feeding stimulants had no effect on the efficacy of this insecticide. Although tefluthrin has been reported to cause short‐lived feeding inhibition in larvae of the southern corn rootworm ( Diabrotica undecimpunctata howardi Barber) at both lethal and sublethal concentrations (Michaelides 1995; Michaelides and Wright 1997), we observed no evidence of antifeedant effects of tefluthrin on neonate western corn rootworm larvae. Larvae fed readily (as high as 90% feeding) on disks treated with tefluthrin and feeding stimulants, and even larvae that exhibited obvious toxicity (writhing and curling) were observed chewing on the feeding stimulant‐treated disks.…”
Section: Discussioncontrasting
confidence: 84%
“…Although the synthetic blend elicited robust feeding by neonate larvae on tefluthrin, the feeding stimulants had no effect on the efficacy of this insecticide. Although tefluthrin has been reported to cause short‐lived feeding inhibition in larvae of the southern corn rootworm ( Diabrotica undecimpunctata howardi Barber) at both lethal and sublethal concentrations (Michaelides 1995; Michaelides and Wright 1997), we observed no evidence of antifeedant effects of tefluthrin on neonate western corn rootworm larvae. Larvae fed readily (as high as 90% feeding) on disks treated with tefluthrin and feeding stimulants, and even larvae that exhibited obvious toxicity (writhing and curling) were observed chewing on the feeding stimulant‐treated disks.…”
Section: Discussioncontrasting
confidence: 84%
“…To determine larval mortality, each grid in an observation device was specifically examined for larvae that showed typical symptoms of Tefluthrin intoxication, usually expressed as writhing and curling . These larvae were recorded as ‘knocked down larvae’, or, when not moving, ‘dead larvae’ during visual inspection.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Gomes et al (2018), working with blowfly (C hrysomya megacephala [Fabricius]), suggested that bubbling serves as a thermoregulatory mechanism. Importantly, in other insect groups, regurgitation may also be a symptomatic response to poisoning or could even be a mechanism for getting rid of toxicants (Lang 1969, Ferguson and Metcalf 1985, Michaelides and Wright 1997). It can also play a critical role in behavioral interactions between insects and plants when regurgitants function as allomones (Cammaerts 1991, 1995), kairomones (Mattiacci et al 1995), resources in nutrient dynamics and communication in many social insects (Suarez and Thorne 2000), or as plant growth promotors (reward feedback) (Dyer et al 1995), or for defense (Sivinski 1980, Peterson et al 1987).…”
mentioning
confidence: 99%